Geological Activity of Microorganisms - K. Sh. Kudratova (Scholars Digest Publishing, 2023)
This article describes several processes such as the formation of soil as a result of the life of the activity of microorganisms, increasing soil fertility, obtaining high yields from plants.
Keywords: Saprophytes, biohumus, complex, macro and micro elements, activation, rhizosphere, agricultural technology, microorganisms, aerobes.